Fuelling the Fire: The effects of Instagram discourse about farm attacks on levels of fear of crime and victimisation - Matai, Dhiya (Department of Public Law, 2024)
Farm attacks are a contentious issue in South African crime discourse. 1 Despite having similar characteristics to home invasions or hijackings in urban areas, popular and academic narratives around farm attacks are woven with broader concerns relating to identity politics, land restitution, minority rights, ethnic solidarity, and labour relations.2 This type of crime seems to exist at the intersection of competing claims and contentions in rural spaces that have struggled to keep pace with the transformation process in the post-Apartheid context.3 While there is little evidence to suggest that farm attacks are politically motivated, discourse (especially in the media) can often paint the problem as a profoundly political one. The discrepancy between the realities of the cases and the popular interpretation of the issue shows us that there is a particular way in which stories about these attacks are being told that imbues them with further meaning. In this study, I analysed how farm attacks are constructed on Instagram accounts that post about rural crime and agricultural issues. These accounts report to a younger generation of mainly white South Africans who are concerned about these attacks; the accounts thus have the power to control the narratives and construct meanings and understandings of the crime. By using a qualitative methodology and content analysis, I dissected over ninety posts to examine whether these accounts were feeding into the fear of crime and victimisation in relation to farm attacks. The research showed that by posting certain graphic images and incendiary language, Instagram accounts are partially responsible for adding fuel to the fire around farm attacks. I argue that these accounts are ultimately counter-productive in gaining attention for victims of these crimes because of the divisive and hostile ways in which they engage the issue. Rural safety needs to be taken seriously, and for this to happen, the narratives need to be divested of the racism and vitriol that so often features in discussions about farm attacks.